The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1149/2.001311jes
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Characterization Studies of Aged Li-Ion Large Format Cells for Improved Performance: An Overview

Abstract: Among various electrical energy storage devices the recent advances in Li-ion battery technology has made this technology very promising for the electric vehicles. The advantage of these batteries is high energy and power density. Understanding the aging mechanisms of these batteries to improve the cycle life is critical for electrification of vehicles. Aging of the cells at the system level is quantified by the increase in internal resistance and drop in capacity. It is imperative to understand the degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 261 publications
(469 reference statements)
1
49
2
Order By: Relevance
“…Early AFM ex situ studies on LiFePO 4 showed an increase in nanoparticle agglomeration with aging of the battery, and subsequent in situ studies at various degrees of charging found significant particle shape and size changes, which were linked to unit‐cell volume differences for Li + release and uptake . Importantly, when analyzing four particles, surface changes were found to be inhomogeneous, thus suggesting non‐uniform utilization of the electrode …”
Section: Spm Studies Of the Positive Electrode Materials In Libsmentioning
confidence: 99%
“…Early AFM ex situ studies on LiFePO 4 showed an increase in nanoparticle agglomeration with aging of the battery, and subsequent in situ studies at various degrees of charging found significant particle shape and size changes, which were linked to unit‐cell volume differences for Li + release and uptake . Importantly, when analyzing four particles, surface changes were found to be inhomogeneous, thus suggesting non‐uniform utilization of the electrode …”
Section: Spm Studies Of the Positive Electrode Materials In Libsmentioning
confidence: 99%
“…As ar esult of their intrinsic high energyd ensity and long lifespan, rechargeable lithium-ion batteries (LIBs) have been used widelya st he main power source in portable electronic devices and are expected to play ap rominent role in the field of stationary energy storage systems and electric transportationt ools. [1][2][3][4][5] Currently, to meet the highere nergy density requirements of future LIBs,g reat efforts are being made toward the developmento fcathodes with higher working voltages and larger specific capacity. [6][7][8][9][10][11][12][13] Lithium cobalt oxide (LCO), which has ar eversible specific capacity of only approximately 140 mAh g À1 (half of its theoretical specific capacity,2 74 mAh g À1 )a ta nu pper cut-off voltage of 4.2 V, is the most successfulc athode material for commercialized LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore,L CO-based LIBs are anticipated to operate at higher voltages than 4.2 Vt oo btain an increased capacity.U nfortunately,a ni ncrease of the upper cut-offv oltage to exceed 4.2 Valways leads to ac lear deterioration of battery performances (especially cyclability and safety)b ecause of the accelerated interfacial parasitic reactions between the charged LCO electrode and nonaqueous electrolytes.C onsequently,u nwanted crystal-structure damage/phase transition, Co dissolution-migration-deposition, and electrolyte decomposition occur. [14,15] At present,t here are two main approaches to improve the interfacial stability between the LCO electrode and nonaqueous electrolytes at elevated cut-off charge voltages.F irst, the LCO surface can be coatedw ith various materials,s uch as metal oxides (e.g.,A l 2 O 3 ,M gO,Z nO,Z rO 2 ), [16][17][18][19][20][21][22][23] metal phosphates (e.g.,A lPO 4 ), [24][25][26] metal fluorides/oxyfluorides (e.g.,A lF 3 ,Z rO x F y ), [27,28] Li ionc onductors (e.g.,L i 2 CO 3 , lithium phosphorus oxynitride,L i 3 PO 4 , Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 ), [15,[29][30][31] and polymers (e.g.,p olyimide). [32] However, it is generally accepted that functional electrolyte additives are of considerable importance in modifying and stabilizing the solid-electrolyte interface( SEI) layer, which determines the cycle life and safety of LIBs significantly.…”
Section: Introductionmentioning
confidence: 99%
“…66,67 There is also the high solubility of the manganese especially in the discharged state because of a disproportionation of the Mn 3þ ion (2Mn 3þ /Mn 2þ þMn 4þ ) that leads to the more soluble Mn 2þ . It is mostly important at high temperature (above 50 C).…”
Section: Spinel Structuresmentioning
confidence: 99%